Mathematical Study of MHD Casson Fluid Flow through Porous Media along with Soret and Dufour Effects Over a Stretching Surface - Jain, Ruchi; Mehta, Ruchika; Mehta, Tripti; Sushila (Science & Technology Asia, 2021)
In this paper multiple slip effects are investigated over inclined permeable extending lamina as well as on melting surface for the MHD non-Newtonian Casson fluid. We analysed the effect of first and second order velocity and concentration slip along with the Soret and Dufour effect. Viscous dissipation, nonlinear heat radiation from a nonlinear heat source is taken. The fluid is having a nonlinear chemical reaction. All the three governing equations of motion, heat and concentration are analysed and solved by bvp4c MATLAB solver. In this investigation we find the impact on different physical parameters and describe them in the form of graphs. Also, the table is formed for the values of skin friction, Nusselt number and Sherwood coefficient.